2017
DOI: 10.1080/02656736.2017.1317845
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1-based tumour-targeting for gold nanostructure-mediated photothermal therapy

Abstract: Purpose To demonstrate delivery of Au nanocages to cells using the galectin-1 binding peptide anginex (Ax) and to demonstrate the value of this targeting for selective in vitro photothermal cell killing. Materials and methods Au nanocages were synthesised, coated with polydopamine (PDA), and conjugated with Ax. Tumour and endothelial cell viability was measured with and without laser irradiation. Photoacoustic (PA) mapping and PA flow cytometry were used to confirm cell targeting in vitro and in tissue slice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…These nanocages had an edge length of 45.6 ± 6.1 nm, and an LSPR at 760 nm which shifted to 794 nm following Ax conjugation, which is included in Figure 2A . These values are consistent with our prior in vitro studies 17, and the shift in the LSPR position is largely the result of the change in refractive index due to the increasing quantity of the polydopamine heteropolymer. This LSPR position allows strong overlap with the laser used in therapeutic studies (808 nm), and falls in the tissue transparent window, which allows light penetration of up to 1 cm through soft tissue 40.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These nanocages had an edge length of 45.6 ± 6.1 nm, and an LSPR at 760 nm which shifted to 794 nm following Ax conjugation, which is included in Figure 2A . These values are consistent with our prior in vitro studies 17, and the shift in the LSPR position is largely the result of the change in refractive index due to the increasing quantity of the polydopamine heteropolymer. This LSPR position allows strong overlap with the laser used in therapeutic studies (808 nm), and falls in the tissue transparent window, which allows light penetration of up to 1 cm through soft tissue 40.…”
Section: Resultssupporting
confidence: 92%
“…Previous in vitro work in our lab and others has demonstrated that adding a targeting- moiety to promote binding to tumor cells appreciably enhances photothermal efficacy 14-16. For instance, we used the polydopamine-coated Au nanocages (AuNC@PDA) targeted to galectin-1 to achieve significant photothermal killing of cells without raising the bulk temperature in the well above 40 °C 17. Targeting was achieved using anginex (Ax), an antiangiogenic, synthetic 33-mer that has been shown to bind galectin-1 in tumors, particularly in the angiogenically active endothelium 18-21.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Jenkins et al. prepared anginex (Ax)‐modified PDA‐coated Au NPs (AuNC@PDA‐Ax) for PTT [ 63 ] and found that the PDA coating enhanced the photothermal performance of the Au NPs. Apart from these, a wide variety of PDA‐based nanomaterials have shown remarkable performance in PTT.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…Another advantage of this approach is its potential for therapeutic versatility [10] More directly,using photoactivatable PDA-coated AuNCs (AuNC@PDA) as the central component, it is possible that different antibodies could be used to enhance the sensitivity and/or coverage of our approach for diverse strains of S. aureus. For instance, while essentially all strains of S. aureus produce Spa, they do so at widely variable levels [9].…”
Section: Introductionmentioning
confidence: 99%